(untitled) (Journal of Economic Research & Business Administration, 2015)
In this article, was made a detailed analysis of the financial situation of the country and the stock market in particular. Data are presented with statistical reports and the Agency of RK. Were viewed the prospects of the Kazakhstan Stock Exchange.